LEARNING COMMUNITY DALAM PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA KELAS XII SMA LPP UMI MAKASSAR - Muli Umiaty; Umar Mansyur (Universitas Negeri Makassar, 2017)
Abstract. Learning Community in Learning English Speaking Skills High School Class XII LPP Umi Makassar. One of the methods that can be applied in an effort to develop students' ability to speak is learning community (community learning and studying together). Learning community is a concept of creating shared learning in school, the learning process between teachers and teachers, teachers and students, students with students, and even among the school community with the community outside the school. This study aimed to describe the extent to which the effectiveness of the learning community in learning English speaking skills high school students of class XII LPP UMI Makassar measured using desaian research that is experimental type of pretest-posttest control group design experiments. Furthermore, data were collected using observation and oral tests were analyzed using descriptive statistics and inferential statistics. The results showed that the learning community is effectively used in improving the skills of English speaking high school students of class XII LPP UMI Makassar. It is based on the results of data analysis showed that the average test speaking skills of students who take classes that implement the learning in the learning community is higher than the results of the test speaking skills of students who take the learning in the classroom learning community that does not apply.